Internal jugular vein aneurysm: a case report - Alshehri, Waleed Mohammed (J Surg Case Rep, 2019)
Venous aneurysms rarely present as a painless mass; they are usually symptomatic and present with pain, swelling, and sometimes, embolism. We present a 41-year-old man who presented with a painless swelling involving the right side of the neck. Examination of the neck revealed a soft, compressible, non-pulsatile and non-tender swelling above the right sternoclavicular joint. Doppler ultrasound showed a well-defined compressible cystic lesion measuring 4.2 × 1.9 cm causing indentation of the right sternocleidomastoid muscle. Further imaging studies confirmed the diagnosis of an aneurysmal dilation in the right internal jugular vein. An excisional biopsy of the aneurysm was performed using a longitudinal incision in the skin at the anterior border of the right sternocleidomastoid muscle and excisional venotomy was performed. Histopathological examination showed a cystic structure containing organizing blood clots surrounded by a thick fibrous wall. A follow-up neck ultrasound performed postoperative showed a patent internal jugular vein.